2017
DOI: 10.1530/rep-16-0359
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of sRAGE in follicular fluid from patients with PCOS

Abstract: This study aimed to explore the association between soluble receptor for advanced glycation end products (sRAGE) levels in follicular fluid and the number of oocytes retrieved and to evaluate the effect of sRAGE on vascular endothelial growth factor (VEGF) in granulosa cells in patients with polycystic ovarian syndrome (PCOS). Two sets of experiments were performed in this study. In part one, sRAGE and VEGF protein levels in follicular fluid samples from 39 patients with PCOS and 35 non-PCOS patients were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…sRAGE can be detected in the blood and follicular fluid [17]. sRAGE is considered an antiinflammatory receptor because it binds circulating AGEs, thus preventing their binding to RAGE, leading to the alleviation of the adverse intracellular events of the pro-inflammatory AGE-RAGE axis [16,18,19]. Recent studies have shown that serum and follicular fluid sRAGE levels were lower in women with PCOS patients and inversely correlated with body mass index (BMI) and insulin resistance [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…sRAGE can be detected in the blood and follicular fluid [17]. sRAGE is considered an antiinflammatory receptor because it binds circulating AGEs, thus preventing their binding to RAGE, leading to the alleviation of the adverse intracellular events of the pro-inflammatory AGE-RAGE axis [16,18,19]. Recent studies have shown that serum and follicular fluid sRAGE levels were lower in women with PCOS patients and inversely correlated with body mass index (BMI) and insulin resistance [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…sRAGE is considered an antiinflammatory receptor because it binds circulating AGEs, thus preventing their binding to RAGE, leading to the alleviation of the adverse intracellular events of the pro-inflammatory AGE-RAGE axis [16,18,19]. Recent studies have shown that serum and follicular fluid sRAGE levels were lower in women with PCOS patients and inversely correlated with body mass index (BMI) and insulin resistance [17,19,20]. We have shown in women without PCOS that follicular fluid sRAGE levels positively correlated with follicular fluid anti-Mullerian hormone (AMH) levels, one of the best markers of ovarian reserve, and also predicted the number of oocytes retrieved following controlled ovarian stimulation (COS), indicating that sRAGE could potentially be used as a marker of ovarian reserve [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sRAGE acts as a decoy that interrupts adverse intracellular signaling caused by the AGE-RAGE axis and is not only a biological marker that reflects pathological changes, but is also a protective factor that delays the occurrence of many diseases [6] . Our previous study found that the follicular fluid sRAGE has a positive correlation with ovarian reservation and decreased in PCOS compared with women without PCOS [7] . One research supported our point that sRAGE could represent a biomarker and a potential therapeutic target for ovarian dysfunction in PCOS [8] .…”
Section: Introductionmentioning
confidence: 89%
“…sRAGE acts as a decoy that interrupts adverse intracellular signaling caused by the AGE-RAGE axis and is not only a biological marker that re ects pathological changes, but is also a protective factor that delays the occurrence of many diseases [6] . Our previous study found that the follicular uid sRAGE has a positive correlation with ovarian reservation and decreased in PCOS compared with women without PCOS [7] . One research supported our point that sRAGE could represent as a biomarker and a potential therapeutic target for ovarian dysfunction in PCOS [8] .…”
Section: Introductionmentioning
confidence: 89%